Penggunaan Tindak Tutur Dan Implikatur Pada Novel Yougisha X no Kenshin karya Keigo Higashino - Endah Adriana, Ajeng; Andry Anita Dewi, Ni Made (Humanis, 2018)
The title of this research is “The Usage of Speech Acts and Implicatur in Yougisha X no Kenshin novel by Keigo Higashino“. This research aims to determine the kind of speech acts and the meaning of implicatur contained in Japanese novel and used the Speech Acts Theory by Austin (1962) and Coorporation Maxim Theory by Grice (1975). The results of this research showed that there are four kinds of speech acts in Yougisha X no Kenshin novel by Keigo Higashino, such as locutionary act, illocutionary act, perlocutionary act and those three types of speech acts in one speech. The speech acts that often appears in Yougisha X no Kenshin novel is the illocutionary act. Furthermore, there are three kind of maxim in Yougisha X no Kenshin novel, such as maxim of quantity, maxim of quality, maxim of relation and maxim of manner. Based on the results of this research, the maxim that often appears in Yougisha X no Kenshin novel by Keigo Higashino are maxim of quantity and maxim of relation.